Sustainability of yhe People's Salt Business Program in Empowering Coastal Communities (Case Study of Talabiu Village, Woha District, Bima Regency) - Hendra Hendra; Ady Ardyansah; Tasrif Tasrif; Muhamadong Muhamadong; Firliah Rizkiani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The People's Salt Business Program (PUGAR) is a government initiative aimed at improving the welfare of coastal communities through strengthening production capacity, enhancing access to capital, and promoting the development of community-based salt enterprises. However, studies examining the sustainability of the program from the perspective of coastal community empowerment remain limited, particularly at the local level. This study aims to analyze the sustainability of the People's Salt Business Program in empowering coastal communities in Talabiu Village, Woha District, Bima Regency, Indonesia. A qualitative research design employing a case study approach was adopted. Research informants were selected purposively and included representatives from the Bima Regency Marine and Fisheries Office, village government officials, fisheries extension officers, community salt business groups, community leaders, and business partners. Data were collected through observation, in-depth interviews, and documentation, and subsequently analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing. Data validity was ensured through source, technique, and time triangulation. The findings indicate that the sustainability of the People's Salt Business Program has made a positive contribution to coastal community empowerment. This is reflected in improved access to business capital, increased salt production, and expanded marketing opportunities for locally produced salt. Furthermore, the program has strengthened the institutional capacity of community salt business groups through continuous guidance and mentoring, while also fostering business partnerships that support sustainable production and market development. Nevertheless, challenges remain in marketing and market accessibility, requiring ongoing support from government institutions and relevant stakeholders. Overall, the sustainability of the People's Salt Business Program has proven effective in enhancing the economic capacity, institutional resilience, and self-reliance of coastal communities in Talabiu Village.